ASTACITA as a Pentahelix Collaboration Model in Building Independent Tourism Villages: A Case Study of Kuta Gugung - Sinulingga, Samerdanta; Nauly, Meutia; Marpaung, Jonathan Liviera (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This article explores the ASTACITA Summit 2025 as an initial model of pentahelix-based collaboration for rural development, focusing on the tourism village of Kuta Gugung in North Sumatra, Indonesia. The summit was conceived as a strategic platform to foster long-term partnerships among five key actors’ government, academia, business, community, and media to empower rural communities in a participatory and sustainable manner. Unlike conventional aid-based programs, ASTACITA emphasizes knowledge transfer, network-building, and multi-sector synergy to promote self-reliance. Using a qualitative descriptive method with a case study approach, data were collected through participant observation, informal interviews, and documentation of summit activities. Results show that ASTACITA effectively enabled cross-sector dialogue, identified community needs and potentials, and catalyzed early-stage partnerships. The summit marked a shift in development discourse from charity-driven to strategy-oriented engagement positioning the village as a co-actor in shaping its own future. This article contributes to the discourse on rural innovation and participatory governance by offering a replicable framework for collaborative village development in Indonesia and beyond.